Familiar ‘strangers’ and creoles: marriage, mobility and networks in the eighteenth century Malay-World - Ciptadi Pitoyo, Wira (Nanyang Technological University, 2024)
Scholarships on early modern Malay World have predominantly focused on the history of local Malay polities in isolation. While there is ample discussion on the migration and networks of communities that settled in the Malay World, there is limited scholarship examining the process itself. By closely tracing the movements of ‘stranger’ and creolised individuals, I aim to uncover the structural dynamic of the eighteenth-century Malay World. Situated within the eighteenth-century history of the Malay World, which also witnessed the emergence of Minangkabau, Bugis and Arabs along with their respective creolised communities, this paper argues that mobility is an extension of politics in the Malay World, and any examination of one cannot exclude the other. Through an examination of concepts surrounding the 'stranger' phenomenon and its interplay with kinship, violence, and retreat, alongside its relationship with mobility, this thesis aims to explore the tensions between resource possession and charismatic leadership charisma of individuals in the Malay World. By exploring the intersection between Johor, Siak and other Malay polities with the aforementioned communities, this paper seeks to demonstrate mobility as a coherent political strategy facilitating interactions in the Malay World